KEMANDIRIAN PETANI DALAM BERUSAHATANI SAGU DI DESA TANJUNG KECAMATAN TEBING TINGGI BARAT KEBUPATEN KEPULAUAN MERANTI PROVINSI RIAU - Rahmat Nursodik; Rosnita Rosnita; Eri Sayamar (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2016)
in  the  globalization  era,  farmers  should  have  strong  independence  and competitiveness. They have to be able to manage their agribusiness to ensure product quality  and  sustainable  agribusiness.  The objectives of the research  are: to analyze the independence sago farmers in farming in the village of Tanjung, This research was conducted in the village of Tanjung District of Tebing Tinggi Barat Meranti Islands District. 66 farmers serve as respondents to the capture technique respondents using purposive  sampling  method.  Data  collected  by  observation,  interviews,  and questionnaires.  analysis  methods  used  to  answer  the  objectives  in  this  research  is methods Likert Scale's Analysis. The results showed: The Independence of farmers in farming sago in the village of Tanjung is independent.